الآثار الأخلاقية لوسائل التواصل الاجتماعي على الشباب الكمبودي المسلم وطرق معالجتها في ضوء سورتي الحجرات والعصر مدرستنا نور الإيمان والمركز الإسلامي نموذجا - Faridah Yaakob
This study explores how Cambodian Muslim adolescents use social media and its impact on their Akhlak, targetting Norol Iman School and Al-Markaz Al-Islami (CIC) students. The study applied preventive methods derived from the Holy Quran to save them from the negative use of social media, which led to the spread of major problems suffered by parents and teachers which has led to the spread of moral degradation, as well as to wasting time, and encouraged inactivity and laziness, as well as infection with many physical and psychological diseases. The research employed inductive and analytical approach by referencing reviews and analysis, as well as a field approach of qualitative and quantitative methods through a questionnaire and an official interview to diagnose the problem up close. The study came up with the following conclusions: 1) most students in Nour al-Iman School and the Islamic Center high school spend a long time on social media, up to four to ten hours a day. Secondly, social media has a negative impact on the morals of some students, regular religious practices, learning processes, and relationship with their parents. Thirdly, the study proposes to implement some preventive educational methods from Surah Al-Hujurat and Surah Al-A’sr by making piety (Taqwa) as a way of life, and a life with Tawhid. Moreover, users are urged to verify news and information checking for authenticity before rushing to publish the information especially on social media platforms, issuing judgments in a way that avoids mistreatment with others, introducing a sense of equality in the hearts of believers, and urging the mujahedeen of the soul and resisting lust and fancy. The study also revealed four elements in the formation of the human personalities derived from Surah Al-A’sr, namely the Lord's Doctrine, the commitment to God's law, also the struggle with truth and patience. Finally, based on the derivation of Qur'anic verses and prophetic hadiths, the study attempted to learn about aspects of spiritual, mental, and physical education to address the ethical problems among Cambodian Muslim adolescents.